Eddy currents in fine polycrystalline metal particle. (August 2019) - Bassel, M; Yushkanov, A A
Abstract: The magnetic dipole absorption in fine metal polycrystalline particle is considered. The kinetic equation with a collision integral that takes into account the influence of electron scattering at the grain boundaries on the properties of the metal has been solved. We consider the case of diffuse reflection of electrons from the sample surface Analysis of the dependence of the absorption cross section of particles from the parameter describing the degree of influence of the scattering on the grain boundaries of polycrystalline particles on the kinetic processes has been considered.